Impacts of Nitrogen Deposition on California Ecosystems and Biodiversity - Weiss, Stuart B. (University of California Santa Barbara and Creekside Center for Earth Observations, 2006)
Recognized as a "biodiversity hotspot," California supports numerous endemic taxa with narrow ranges, and that diversity may be threatened by atmospheric nitrogen deposition. This California-wide risk screening included: (1) a 36 x 36 kilometer (km) map of total Nitrogen (N)-deposition for 2002, developed from the Community Multiscale Air Quality Model (CMAQ); (2) identification of sensitive habitats; (3) an overlay of the Forest Resource and Protection (FRAP) vegetation map; (4) an overlay of animal and plant species occurrence data from the California Natural Diversity Data Base (CNDDB); (5) an initial analysis of species life history and habitat; and (6) a discussion of relevance and guidance for assessments of power plant impacts. An area of 55,000 square kilometers (km2) of California is exposed to more than 5 kilograms of N per hectare per year (kg-N ha-1 year-1), and 10,000 km2 are exposed to more than 10 kg-N ha-1 year-1. Deposition hotspots include: Los Angeles-San Diego, the San Francisco Bay Area, the Central Valley, and the Sierra Nevada foothills. The major documented impact of N-deposition on California terrestrial biodiversity is to increase invasive annual grasses in low biomass ecosystems, resulting in species loss. Of 225 "threatened" and "endangered" plant taxa, 99 are exposed to an average > 5 kg-N ha-1 year-1. Of 1,022 "rare" plant taxa, 290 are exposed to > 5 kg-N ha-1 year-1. Listed animal species follow similar patterns. This initial screening outlines potential impacts on California's biodiversity and provides targeted guidance for assessing the impacts of power plant and other sources of atmospheric N-deposition.
Keywords: annual grasses; biodiversity; California; deserts; eutrophication; grasslands; invasive species; nitrogen deposition; threatened and endangered species